Estimating the distributional impacts of the COVID-19 pandemic and the remedial tax and benefit policies on poverty in Indonesia - Gemma Wright; Michael Noble; Helen Barnes; Ali Moechtar; David McLennan; Arief Anshory Yusuf; Katrin Gasior; Ratnawati Muyanto (University of Essex, Centre for Microsimulation and Policy Analysis (CeMPA), 2021)
During 2020, the COVID-19 pandemic wreaked havoc across the world, causing shockwaves that have impacted on many people's lives and financial security. In the absence of any known cures or preventative vaccines, governments quickly implemented policies to minimize its impact. In particular, public health policies were rolled out which focused on containing the spread of the virus but these measures in turn had a detrimental impact on many economies. In addition, tax and benefit policies were often either augmented or introduced from scratch, in order to mitigate the financial impact of the pandemic and associated containment measures on people's lives. The speed with which initiatives were introduced has been unprecedented: for example, the United Nations Special Rapporteur on extreme poverty and human rights observed that 1,407 new social protection measures had been adopted by 208 countries and territories by September 2020 (UN, 2020). In this paper we explore how the COVID-19 pandemic has impacted on people's earnings in Indonesia, the extent to which the automatic stabilisers that were already built into the tax and benefit system cushioned the economic shock, and how the augmented or new tax and benefit policies that were introduced because of the pandemic served to further cushion the shock. The analysis was conducted for each calendar month of 2020 and makes use of a tax-benefit microsimulation model for Indonesia called INDOMOD (Barnes et al., 2019), which is underpinned by the EUROMOD microsimulation software Version 3.1.8 (University of Essex, 2019).
Keywords: 330; Microsimulation; Public Policy; Welfare Benefits; Taxation; Covid-19; Health